Christian Muslim Moderation Local Wisdom Based - Sam'un Mukramin; Alfiani Aminah (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
The discussion in this study provides a statement, namely although the people in west Manggarai Regency, more precisely in Tangge Village, have different beliefs, but the differences do not make people look at it in different ways, but that is what makes the people live in harmony. Efforts to strengthen religious moderation can make religious ritual traditions as strengthening the relationship between religion and the traditions and culture of the local community. Just as the Tangge people have a tradition that is mandated by the Wuat Wa'i ritual. This religious ritual tradition is a culture of religion that has been embedded for generations in Tangge, Lembor district, West Manggarai Regency. Religious ritual traditions contain moral messages of religious and cultural moderation that can be the foundation of harmony between religious people. Although the people in West Manggarai Regency have different beliefs, the community has proven harmony by creating good interactions.